REAKSI HARGA SAHAM SAAT PENGUMUMAN DIVIDEN TUNAI DIMODERASI OLEH FREE CASH FLOW - Andini, Ni Wayan Lady; Suputra, I D.G Dharma; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.11.TAHUN 2017, 2017)
This study examines the stock price reaction when companies announce cash dividend distribution, which is moderated by free cash flow. Dividend distribution information is believed to affect the stock price. The result s of s everal previous research have inconsistencies . Therefore, the free cash flow variable is included as a moderating variable which is predicted to strengthen the effect of cash dividend announcement on stock price reaction. The population of this research is all companies listed on the BEI in 2013-2015. The sample was determined by purposive sampling method, and produced 32 samples in 2013, 34 samples in 2014, and 25 samples in 2015. The data analysis technique used was Moderated Regression Analysis (MRA). The results of this research indicate that the announcement of cash dividend positively affects the stock price reaction , while free cash flow is not proven as a moderator of the effect of cash dividend announcement on stock price reaction. The future research can be done by replacing the event date using the period of the Annual General Meeting (AGM), and using the dividend policy (increased or decreased) as an independent variable to prove the role of free cash flow as a moderator.